Evolution of Chinese Islamic architecture -A case of "Great Mosque of Hohot (Qingzhen Dasi), Inner Mongolia, peoples Republic of China" - Soomro, Ali Raza; Ibrahim, Mansor; Mohd Nawawi, Norwina (s.n, 2012)
China is one of the older civilizations in the world with four thousand (4000) years history. It is an ancient civilization which is extended over a large area in East Asia. The Chinese civilizations are known for its years of prosperity and have since generated competitive minds and stimulated the growth and development in other parts of the world. Country known for its prosperous civilizations, China is blessed with beautiful landscapes and multi-cultural ethnicities.